2016
DOI: 10.1021/acs.jpcc.6b07820
|View full text |Cite
|
Sign up to set email alerts
|

pH Dependence of Interfacial Water in the Presence of Amino Acid Side Chains Revealed by Heterodyne-Detected Sum-Frequency Generation Spectroscopy

Abstract: Proteins are built of amino acid residues that differ from each other only by their side chain. The pH-dependent response of these side chains on protein surface is vital for various biological processes. Here we have investigated the aqueous interface in the presence of different amino acid side chains at varying pH (bulk) using heterodyne-detected vibrational sum-frequency generation (HD-VSFG) spectroscopy. It is observed that amine/imidazolic (e.g., lysine/histidine) and alcoholic (e.g., serine and threonin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
26
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 49 publications
4
26
0
Order By: Relevance
“…It is important to note that previous phase‐sensitive/heterodyne‐detected VSFG measurements [20, 27, 37, 38] showed a positive Imχ (2) band around 3200 cm −1 and was assigned to the “ice‐like” or “strongly H‐bonded water pair”. The positive band however is not so prominent in the carefully measured recent Imχ (2) spectra, [35, 36, 39–41] which is in conformity with the present data (black‐dashed curve in Figure 2 a ) measured using high resolution displacement sensor (see the Supporting Information) as well as our previously reported spectra that were phase‐corrected by internal referencing [42–44] . With the addition of 20 μM αS in water, the surface pressure ( π =surface tension of neat water (72.8 mN m −1 )—surface tension of αS solution) becomes ≈20 mN m −1 , indicating adsorption of αS on water surface.…”
Section: Resultssupporting
confidence: 92%
“…It is important to note that previous phase‐sensitive/heterodyne‐detected VSFG measurements [20, 27, 37, 38] showed a positive Imχ (2) band around 3200 cm −1 and was assigned to the “ice‐like” or “strongly H‐bonded water pair”. The positive band however is not so prominent in the carefully measured recent Imχ (2) spectra, [35, 36, 39–41] which is in conformity with the present data (black‐dashed curve in Figure 2 a ) measured using high resolution displacement sensor (see the Supporting Information) as well as our previously reported spectra that were phase‐corrected by internal referencing [42–44] . With the addition of 20 μM αS in water, the surface pressure ( π =surface tension of neat water (72.8 mN m −1 )—surface tension of αS solution) becomes ≈20 mN m −1 , indicating adsorption of αS on water surface.…”
Section: Resultssupporting
confidence: 92%
“…17,26,50,78 Disentangling c ð2Þ ijk and c ð3Þ ijkz contributions to the vSFG response at charged interfaces is particularly challenging and has recently been the focus of several experimental and theoretical studies on model systems. 10,17,26,[28][29][30]32,40,42,43,47,50,69,75,76,78,103,105,106 Perhaps most importantly, these studies have now revealed that the second-and third-order contributions to the SFG response from charged interfaces are not merely additive but instead modulated non-linearly by the ionic strength-dependence of the c ð3Þ ijkz phase angle 76 and the phase interference 32,105 terms shown in Equation 1. Recent work on the salt concentration-dependent water OH stretching spectra obtained from bilayers, as opposed to monolayers, of zwitterionic and anionic lipids has identified the an additional complication, namely, the choice of a truly zero-potential reference state.…”
Section: Rementioning
confidence: 98%
“…Thep ositive band however is not so prominent in the carefully measured recent Imc (2) spectra, [35,36,[39][40][41] which is in conformity with the present data (black-dashed curve in Figure 2a )m easured using high resolution displacement sensor (see the Supporting Information) as well as our previously reported spectra that were phase-corrected by internal referencing. [42][43][44] With the addition of 20 mM aSi nw ater, the surface pressure (p = surface tension of neat water (72.8 mN m À1 )-surface tension of aS solution) becomes % 20 mN m À1 ,i ndicating adsorption of aS on water surface.Inthe HD-VSFG measurement too,the CH stretch region (< 3000 cm À1 )w hich was featureless for the neat air-water interface,s hows sharp negative bands around 2880 and 2940 cm À1 (yellow curve) corresponding to the C À H stretch of aS, confirming the presence of aSatt he air-water interface.The OH stretch band ( % 3000-3580 cm À1 )becomes positive in sign due to interfacial aS(yellow curve,expanded view of the OH stretch is shown in the inset, Figure 2a). The Positive sign implies that the interfacial water which was Hdown oriented (negative Imc (2) )a tt he neat air-water interface,a dopts H-up orientation in presence of aS.…”
Section: Angewandte Chemiementioning
confidence: 99%